Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae) - Jordal, Bjarte H. (Zootaxa, 2018)
Twenty-one new species of Scolytodes Ferrari are described from Central and South America: Scolytodes cavus Jordal, sp. nov., Scolytodes excavatus Jordal, sp. nov., Scolytodes speculofrons Jordal, sp. nov., Scolytodes potens Jordal, sp. nov., Scolytodes minimus Jordal, sp. nov., Scolytodes setosicauda Jordal, sp. nov., Scolytodes monticola Jordal, sp. nov., Scolytodes aureifrons Jordal, sp. nov., Scolytodes piliscapus Jordal, sp. nov., Scolytodes curvicostatus Jordal, sp. nov., Scolytodes vellus Jordal, sp. nov., Scolytodes granulatus Jordal, sp. nov., Scolytodes bipilosus Jordal, sp. nov., Scolytodes asperatus Jordal, sp. nov., Scolytodes flavifrons Jordal, sp. nov., Scolytodes capillus Jordal, sp. nov., Scolytodes rufus Jordal, sp. nov., Scolytodes johnsoni Jordal, sp. nov., Scolytodes longipilus Jordal, sp. nov., Scolytodes prolatus Jordal, sp. nov., and Scolytodes bicarinatus Jordal, sp. nov. Females of two species were associated with males and described for the first time: Scolytodes pelicipennis (Schedl, 1952) from Mexico, and Scolytodes venustulus Wood, 1967 from Costa Rica. New synonymies were inferred in four species: Scolytodes bolivianus Eggers, 1928 (=Scolytodes aequipunctatus Eggers, 1943 syn. nov.); Scolytodes major Eggers, 1928 (=Scolytodes argentinensis Eggers, 1943 syn. nov.; =Scolytodes boliviensis Eggers, 1928; =Scolytodes similis Eggers, 1928 syn. nov.); Scolytodes ingae (Blackman, 1943), stat. nov. (=Scolytodes trigonus Jordal, 2013 syn. nov.); Scolytodes canalis Wood, 1974 (=Scolytodes amabilis Wood, 1975 syn. nov.). New country records are reported for 13 species: S. alni Wood, 1969 (Panama), S. bolivianus (Brazil), S. canalis Wood, 1974 (Guatemala), S. chapuisi Wood, 1977 (Peru, Brazil), S. costabilis Wood (Costa Rica), S. elongatus Schedl, 1935 (Panama), S. immanis Wood, 1969 (Panama), S. ingae (Blackman, 1943) (Panama), S. irazuensis Wood, 1969 (Panama), S. major (Honduras, Brazil), S. pelicipennis (Schedl, 1952) (Mexico), S. triangulus Jordal, 1998 (Panama), S. unipunctatus (Blandford, 1897) (Panama, Venezuela), S. venustulus Wood, 1967 (Costa Rica).